Meta-Analysis of Efficacy and Safety of Tadalafil Plus Tamsulosin Compared with Tadalafil Alone in Treating Men with Benign Prostatic Hyperplasia and Erectile Dysfunction - Zhou, Zhongbao (Am J Mens Health, 2019)
This meta-analysis was performed to evaluate the efficacy and safety of tadalafil plus tamsulosin compared with tadalafil alone in treating men with benign prostatic hyperplasia (BPH) and erectile dysfunction (ED) after 12 weeks’ treatment. Systematic review was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-analyses. MEDLINE, EMBASE, and the Cochrane Controlled Trials Register were searched to collect randomized controlled trials. The references of related articles were also searched. Four articles including 621 patients were involved in the analysis. The study identified that combination-therapy had significant improvements in total international prostate symptom score (IPSS), quality of life (QoL) and maximum urine flow rate (Qmax) compared with monotherapy, and there were no obvious significance in respects of post-void residual volume, international index of erectile function and IPSS storage. The difference of total IPSS was mainly reflected in the change of IPSS voiding. For safety, combination-therapy had a higher incidence rate of any adverse events (AEs) and discontinuation due to AEs than monotherapy with the exception of pain. In conclusion, the combination of tadalafil and tamsulosin provided a better improvement of IPSS voiding, QoL and Qmax compared with tadalafil alone in treating men with BPH and ED, and the former therapy appeared to show a higher incidence of AEs.